Instrumen Kebijakan Moneter ‎(Analisis Managemen Moneter Islami)‎ - Mugiyati Mugiyati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The monetary management of conventional economy which revolves around bank interest uses multiplier money rather than high powered money. Consequently, its instrument of monetary policies tends to the utility of open market operation and change of discount rate. Both instruments cannot be applied in an Islamic monetary system which is free from interest whose monetary management relies on controlling high powered money by applying profit and loss sharing and financial intermediation. Therefore, Islamic monetary system can employ alternative instruments of monetary policy such as quantitative control of credit allocation and realization of socio-economic objectives. The first instrument is backed up with monetary instruments such as statutory reserve requirement, credit ceiling, government deposits, common pool, moral suasion, equity-base instrument. Whereas the second instruments include some monetary instruments such as treating the created money as fai’ and goal oriented allocation of credit.